Spillover Impacts of Informal Employment on Indonesia's Food Security - Anggara, Rizki Tri; Alfahma, Elsya Gumayanti (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
This study analyzes the impact of informal employment on household food security in Indonesia, focusing on regional disparities in provinces with high concentrations of informal workers. Using national socioeconomic survey data, logistic regression models initially assessed the associations between informal employment and food security outcomes. To strengthen causal inferences and mitigate selection bias, a comprehensive Propensity Score Matching (PSM) analysis was subsequently conducted. The findings from both approaches consistently link informal employment to adverse food security outcomes, including food availability concerns, limited access to nutritious food, and lower dietary diversity. Provinces with a high prevalence of informal workers consistently demonstrate poorer food security metrics, with the PSM analysis revealing more pronounced negative impacts in these regions, indicating significant spillover effects. Factors such as tertiary education, internet access, and health insurance are positively associated with improved food security, highlighting the critical role of human capital and resource access. These results underscore the importance of employment stability and regional labor market structures in shaping food security. Policies promoting formal employment and stronger social safety nets are critical for equitable food security across Indonesia.